Requisites for the Establishment, Implementation, and Evaluation of Social Work Treatment Programs for Anti-Social Children - Wodarski, John S. (1979)
Requisites for the establishment, implementation and evaluation of social work treatment programs for anti-social children are reviewed. Specific items discussed are: how does one ascertain the level at which change efforts should be directed, i.e., individual, group, organizational, or societal; what is the appropriate context for behavioral change; who should act as the change agent; what characteristics should the worker possess; what are the rationale for service provided; how long should the treatment continue; how does one prepare for the termination of treatment and maintenance of behavior; what organizational factors of treatment contexts are pertinent to the constructive delivery of services; what are the requisites for the adequate evaluation of treatment programs, and what are the characteristics of efficacious therapeutic programs for anti-social children. Throughout the manuscript relevant future research issues are reviewed